Chondroitin Sulphate Decorated Polymeric Nanoparticles: An Effective Carrier for Enhancement of Lung Cancer Targeting Capabilities of Anticancer Drug - Garg, Sweta; Garg, Ashish; Enaganti, Sreenivas; Yadav, Awesh K. (Current Nanomedicine, 2019)
Background: Currently, cancer is rising as one of the dominant causes of human deaths worldwide. The application of nano-carriers may help to treat cancer through the delivery of anticancer drugs inside the tumor cells. Objective: The foremost objective behind this research was to formulate chondroitin sulfate tailored cellulose acetate phthalate (CSAC) core shield nanoparticles (NPs) containing 5-Fluorouracil (5-FU) as an anticancer drug. Methods: The FTIR and 1H-NMR spectroscopic methods were used to analyze and characterize the formulation of CSAC copolymer. NPs were typified by Differential Scanning Calorimetry (DSC), X-ray Diffraction (XRD), Atomic Force Microscopy (AFM), Entrapment efficiency and in-vitro drug release. Results: CSAC NPs were found to exhibit moderate release (95.59±0.15% in 34hrs) than CAP NPs (78.97±0.08% in 8 hours). In the course of cytotoxicity examination in A549 cancer cell line, the results revealed that these 5-FU loaded CSAC NPs showed an immense cytotoxic potentiality. Moreover, CSAC NPs exhibit least hemolytic activity when compared with CAP NPs and plain 5-FU. Conclusion: Conclusively, it was found that the CSAC NPs is an efficient carrier system for the better release of 5-FU in lung cancer.
Keywords: cellulose acetate phthalate